Analysis and Numerical Approximation of an Electro-Elastic Frictional Contact Problem (Advances in Applied Mathematics and Mechanics, 2018)
We consider a mathematical model which describes the static frictional contact between a piezoelectric body and a conductive foundation. A non linear electro-elastic constitutive law is used to model the piezoelectric material. The unilateral contact is modelled using the Signorini condition, nonlocal Coulomb friction law withslip dependent friction coefficient and a regularized electricalconductivity condition. Existence and uniqueness of a weak solutionis established. The finite elements approximation of the problem ispresented. A priori error estimates of the solutions are derived and a convergent successive iteration technique is proposed.